Quality of life assessment in chronic wound patients using the Wound-QoL and FLQA-Wk instruments - Vogt, Tatiele Naiara; Koller, Francisco José; Dias Santos, Pamella Naiana; Lenhani, Bruna Eloise; Guimarães, Paulo Ricardo Bittencourt; Kalinke, Luciana Puchalski (Investigación y Educación en Enfermería, 2020)
Objective. To evaluate changes in the quality of life of patients with chronic wounds. Methods. Quantitative research with a cross-sectional design performed with 100 patients with chronic wounds from a university hospital and a Basic Health Unit in southern Brazil. The mean values of the domains of the instruments Wound Quality of Life (Wound-QoL) and Freiburg Life Quality Assessment Wound were compared with sociodemographic variables of age, sex and education. Results. The average age of the participants was 60.98 years old; 41% had diabetic ulcers and 83% treated the wounds for more than 24 months. The total quality of life value was below the mean with 37.50/100 with (Wound-QoL) and 44.20/100 with (FLQA-Wk). The variables of gender, and educational level were not correlated with either of the two instruments used to assess the quality of life. The age variable was significantly correlated with the satisfaction item of the FLQA-Wk. Conclusion. The quality of life of patients with chronic wounds was considered poor. The age variable was correlated with the satisfaction domain, showing that the older the age, the lower the satisfaction. The use of instruments to evaluate the quality of life of patients with chronic wounds may help an effective treatment plan.